Transcriptomic responses to thermal stress in hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) - Zhang, Qian; Huang, Jianfang; Yang, Chenyu; Chen, Jianming; Wang, Wei (Frontiers in Genetics, 2022)
China is the world’s largest abalone producing country. Currently, summer mortality caused by high temperature, is one of the biggest challenges for abalone aquaculture industry. The hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) was conferred on the “new variety”. It has heterosis for thermal tolerance and has been cultured at large-scale in southern China. In this study, a transcriptome analysis was performed to identify the related genes in this hybrid abalone under thermal stress and recovery stage. Compared to control group (18℃), a total of 75, 2173, 1050, 1349, 2548, 494 and 305 differentially expressed genes (DEGs) were identified at 21°C, 24°C, 27°C, 30°C, 32°C, 29°C, 26°C, respectively. In this study, 24℃ is the critical temperature at which the abalone is subjected to thermal stress. With the temperature rising, the number of stress-responsive genes increased. During the temperature recovering to the optimum, the number of stress-responsive genes decreased gradually. Thus, this hybrid abalone has a rapid response and strong adaptability to the temperature. Under the thermal stress, the abalone triggered a complicated regulatory network including degrading the misfolded proteins, activating immune systems, negative regulation of DNA replication, and activating energy production processes. The more quickly feedback regulation, more abundant energy supply and more powerful immune system might be the underlying mechanisms to fight against thermal stress in this hybrid abalone. These findings could provide clues for exploring the thermal-response mechanisms in abalone. The key genes and pathways would facilitate biomarker identification and thermal-tolerant abalone breeding studies.